COMPARISON OF EFFICACY OF ACECLOFENAC WITH DICLOFENACSODIUM FOR POSTOPERATIVE PAIN RELIEF FOLLOWINGLAPAROSCOPIC CHOLECYSTECTOMY - Afia Arshed Dodhy (Baqai Journal of Health Sciences)
The object of the present study was to compare the efficacy of intramuscular injections of aceclofenac with diclofenac sodium for postoperative pain relief following laparoscopic cholecystectomy. The study was carried out in the Department of Anesthesiology, Combined Military Hospital, Quetta, Pakistan. A randomized clinical trial was performed over a period of six months from January to July, 2015. A total of 154 patients, age between 2150 years, were enrolled and divided into two groups of 77 each. The mean age of patients in Group A and B was 36.1±6.8 and 36.1±7.1 years, respectively. The number of male and female patients in Group A were 52 (67.5%) and 25 (32.5%), respectively while in Group B the number was 50 (65.0%) and 27 (35.0%), respectively. The inclusion criterion of patients was based on the classification I and II of the American Society of Anesthesiologists (ASA). The patients of one group received IM injection of aceclofenac (150 mg) while the other group received IM injection of diclofenac sodium (75 mg), half an hour prior to extubation. The postoperative intensity of pain at 0.5, 1, 2, 4, 6, and 12 h was measured using visual analog scale (VAS). VAS value of >5 was considered as inadequate and an alternative analgesic (tramadol) was administered. A considerable decrease in postoperative VAS values was observed in Group A when compared with the patients of Group B (i.e. 61.0% vs 42.9%, p=0.023). Stratification with regard to age, gender, height, weight, and ASA status was performed. It has been observed that after laporoscopic cholecystectomy the relief in severe pain is better with IM injections of aceclofenac as compared to diclofenac sodium.